"These Things Don't Work." Young People's Views on Harm Minimization Strategies as a Proxy for Self-Harm: A Mixed Methods Approach. Issue 3 (2nd July 2020) - Wadman, Ruth; Nielsen, Emma; O'Raw, Linda; Brown, Katherine; Williams, A. Jess; Sayal, Kapil; Townsend, Ellen
Abstract : Although UK clinical guidelines make tentative recommendations for "harm minimization" strategies for repeated self-harm, this is in the absence of empirical evidence supporting their acceptability or effectiveness. We explore young people's views of harm minimization strategies (e.g., snapping elastic bands on skin, drawing on skin with red ink), as a proxy for self-harm. In this mixed methods study we examine data (secondary analysis) from: (1) an online questionnaire ( N = 758) observing the frequency of these strategies being used as a form of self-harm, and as a form of alternative coping (viewed as distinct from self-harming), and (2) semi-structured interviews ( N = 45), using thematic analysis to identify themes related to harm minimization. Predominant themes suggest that many young people viewed harm minimization strategies as a proxy for self-harm as ineffective. Where such strategies were reported as helpful, their utility was reported to be short-lived or situation-specific. Findings from both studies indicate that some young people described using harm minimization (e.g., elastic band snapping) as a form of self-harm (e.g., to break the skin). Harm minimization strategies should not be recommended in isolation and their use must be monitored. Further research is urgently needed to develop an evidence base that informs practice.